Chapter Ripensare la signoria rurale trentina - Varanini, Gian Maria (Reti Medievali E-Book, 2023)
The essay reconstructs the development of studies on rural lordships in Trentino during the 19th-20th centuries, the period of the dissolution of a seigniorial system that had survived almost six hundred years.